Analisis Perancangan Dry Container Sebagai Alternatif Transportasi Liquid Petroleum Gas (LPG) 12 KG di Daerah Perintis - kharis abdullah; Id Adha Mulab; Rodlitul Awwalinc (Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2022)
LPG is one of the gas fuels needed in daily life after the government has converged the use of fuel oil to fuel gas. The distribution of 12 Kg LPG in remote and outermost areas is still often hampered by the delivery process. Constraints in the distribution of 12 Kg LPG caused prices to become unstable. Government program to reach out and equal distribution of goods by making jalur tol laut. One of the sea toll fleets is the pioneer container ship that transports containers from remote and outermost areas. One alternative to transporting 12 Kg LPG is to use dry containers as a means of transportation. The transportation of 12 Kg LPG using containers goes through the design stages and structural analysis to determine the feasibility of the construction. Containers with a length of 20 feet are capable of carrying 126 12 Kg LPG cylinders, with an additional deck construction in the middle of the container with a deck plate thickness of 2 mm. By using the ANSYS APDL software, the analysis of the strength of the additional construction structure in the container is still below the required allowable stress of 103.23 N/mm2 and the actual deflection that occurs is 0.516 mm.